NEONATAL SCROTAL WALL NECROTIZING FASCITIS (FOURNIER GANGRENE SCROTUM) IN A ONE MONTH OLD NEONATAL: A RARE CASE REPORT - Fathoni, Muhammad Halim; Rahman, Eka Yudha; Sutapa, Hendra; Yulizar, Deddy Rasyidan; Umam, Akmal Fauzi Yusri (Indonesian Journal of Urology, 2024)
Objective: In this report, we present our case of a one-month-old neonatal with Fournier gangrene who was referred to our hospital. Case(s) Presentation: A one-month-old patient came from a referral hospital with chief complaint had a diaper rash since 6 days before hospital admission, fever existed, and patient’s scrotal became swollen and appear white spot. The patient was referred to Ulin General Hospital Banjarmasin for a necrotomy debridement. Discussion: We recommend more than one antibiotic to cover it, including one specifically targeted toward it. Both Enterococcus and S. aureus have been implicated as the causative organisms of Fournier gangrene in previous reports. Conclusion: Fournier gangrene in neonatal is a rare case and potentially life-threatening disease, it is a progressive gangrenous of the genitalia, perineum and perianal regions. Keyword: Fournier gangrene, scrotal, neonatal